Blood donor notification of variant Creutzfeldt–Jakob disease risk: Lessons in communicating donor deferral and risk. Issue 1 (24th June 2022) - Reynolds, Claire A.; Yawitch, Tali; Hewitt, Patricia E.; Harvala, Heli
Abstract: Background: In 2005, the blood service in England notified 101 donors by letter that they may be at risk of variant Creutzfeldt–Jakob disease (vCJD) because a recipient of their blood later developed vCJD. Donor experience of the notification was studied in a 2009 survey. Methods: Fifteen questions focused on satisfaction, emotional response and understanding of the notification letter. An average Likert score was calculated: 1 and 2 = dissatisfied, 3 = equivocal and 4 and 5 = satisfied; the per cent satisfied and dissatisfied were calculated and characteristics compared using the Fisher and Chi‐squared tests. Results: The questionnaire was completed by 56 of 90 notified donors, mostly repeat, U.K.‐born donors over 45 years of age. Four years after notification, many individuals still felt surprise (44%), upset (44%) or worry (50%) about the letter, with 10 feeling depressed. Thirty per cent were uncertain if they had vCJD or not. For future notifications, 57% would still favour a detailed letter and 36% would prefer a discussion in person. Discussion: It was notable how many individuals, 4 years later, still felt continuing anxiety about the vCJD notification letter, not noted in earlier interviews. This highlights a need for on‐going support required in donor notifications where outcome for the individual is highly uncertain.